Research on the Success of the Crowdfunding Platform Performance in the Funder Dana Project Indonesia Facebook Community - Wahjono, Sentot Imam; Marina, Anna; Fen, Fam Soo; Oktaviani, Marista; Alamin, Muhammad Salman Bintang Rahmat (Universitas Muhammadiyah Jakarta, 2023)
This research aims to determine the influence of fundraising, product testing, relationship reliability, and increasing awareness on crowdfunding platform performance. The performance of crowdfunding is necessary for research because it involves raising funds from the wider community which needs to be kept safe. This research uses a quantitative approach using regression analysis. The population in this research consists of start-up business actors, MSMEs, investors and other supporters who are members of the Funder Dana Project Indonesia, a Facebook social media group with 1,504 members. This research sample is based on the Krejcie-Morgan Table with an error rate of 5%, consisting of 289 respondents. The research results show that fundraising, product testing, relationship reliability, and increasing awareness simultaneously have a positive and significant effect on crowdfunding platform performance. The recommendation of this research is that crowdfunding stakeholders including the government (OJK) should join social media communities such as Funder Dana Project Indonesia as a medium to build long-term connections and interactions between start-up business actors, MSMEs, investors and other supporters, and continue . to create products that are unique, creative and have selling power so that they get a good response from the public and investors. Recommendations for the government (OJK) to always encourage all crowdfunding platform providers to be in good and healthy condition.